Medical cultures of the Early modern Spanish empire - Slater, John, 1972-; López Terrada, María Luz; Pardo Tomás, José (New hispanisms., 2014)
As the Spanish empire grew, cultural ideas and practices related to sickness and health, sex, monstrosity and death came into contact and conflict. Old ideas took root in new soil, others were stamped out, and new cultures arose. This collection examines the dynamic context in which medical cultures circulated to propose new interpretations of the reception, appropriation, and elaboration of medical cultures in the vast territories controlled by the Spanish monarchy.